Unilateral lumbopelvic fixation for AO/OTA Type C1 and C2 pelvic fractures: Clinical efficacy and preliminary experiences in 23 patients. Issue 8 (August 2021) - Qiao, Bo; Liu, Jiayu; Ni, Weidong; Shui, Wei; Luo, Gang; Guo, Shuquan
Highlights: AO/OTA Type C1 and C2 pelvic fractures have unilateral vertical instability of pelvic ring. Unilateral lumbopelvic fixation provides a well reduction quality and was an effective treatment for AO/OTA Type C1 and C2 pelvic fractures. Compared to bilateral or triangle lumbopelvic fixation, unilateral fixation is simpler and less invasive. Lumbopelvic fixing instruments are not just a fixation method but also can reduce the pelvic displacement by traction between lumbar and iliac screws. Abstract: Purpose: To report the clinical outcomes and preliminary experiences of unilateral lumbopelvic fixation for patients with AO/OTA Type C1 and C2 pelvic fractures. Materials and Methods: Between May 2014 and Dec 2017, 23 consecutive patients with AO/OTA Type C1 and C2 pelvic factures were treated by unilateral lumbopelvic fixation. Estimated blood loss, operation duration, reduction quality, functional outcomes using Majeed scores and complications were evaluated. Subgroup analysis was used to assess the influence of unilateral lumbopelvic fixation on different type of pelvic fractures. Results: Fifteen patients with Type C1 pelvic fractures and eight patients with Type C2 fractures underwent unilateral lumbopelvic fixation respectively. The mean follow-up time till May 2019 was 34.3 ± 9.9 months (range 17–60 months). Mean estimated blood loss was 473 ml and mean operation duration was 156 min during unilateral lumbopelvic fixation. The mean vertical displacement of pelvis decreased from 10.1 ± 4.9 mm to 3.1 ± 1.9 mm after unilateral lumbopelvic fixation. Majeed score assessments were available for 22 patients. Of these, 13 patients were graded as excellent, 8 were good and one was fair. The results of subgroup analysis showed that there was no difference of estimated blood loss, operation duration, postoperative displacements of pelvis and Majeed scores between the patients with Type C1 and C2 fractures. Conclusion: Unilateral lumbopelvic fixation could provide a well reduction quality and was an effective treatment for AO/OTA Type C1 and C2 pelvic fractures. Study Design: Retrospective evaluation of 23 consecutive patients with AO/OTA Type C1 and C2 pelvic fractures treated by unilateral lumbopelvic fixation.